Laboratórios de simulação e experimentação remota no ensino de ciências: uma análise do potencial técnico e pedagógico - Gonçalves, Jones Artur (Universidade Federal de São Carlos, 2020)
The purpose of this research was to analyze from the pedagogical and technical point of view the potential of remote laboratories and simulators for basic education Science classes. The work has presented a brief record of information and communication technologies (ICT) in Science teaching and its pedagogical perspectives. In order to meet the paper purposes different remote pedagogical and simulators profiles were studied in different countries and technological contexts. The main advantages and challenges of its use were discussed, as well as the needs for the expansion of these resources in school institutions. In a general way, through the analysis it was possible to find evidences of the contribution from remote and testing laboratories in Science teaching. The results found in this paper proposes that the testing through the remote laboratories and simulators under the pedagogical perspective can contribute to a greater engagement of the students; greater involvement with teamwork through a collaborative learning, in addition to a more stimulating practice through the scientific involvement with the content. The expected contribution from this work is to foster the academical discussion about the use of technologies as remote laboratories and testing in teaching by making Science contents in basic education more interactive, dynamic and motivating.
Simulators and remote laboratories in science teaching: an analysis of the technical and pedagogical potential
Keywords: Laboratórios remotos; Simuladores; Tecnologias da Informação e Comunicação; Educação científica; Remote laboratories; Simulators; Information and Communication Technologies; Science teaching; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO::ARQUITETURA DE SISTEMAS DE COMPUTACAO